Forced Disruption of Anatomy Education in Australia and New Zealand: An Acute Response to the Covid-19 Pandemic - Pather, Nalini; Blyth, Phil; Chapman, Jamie A; Dayal, Manisha R; Flack, Natasha A M S; Fogg, Quentin A; Green, Rodney A; Hulme, Anneliese K; Johnson, Ian P; Meyer, Amanda J; Morley, John W; Shortland, Peter J; et al. (Anatomical sciences education, 2020)
Australian and New Zealand universities commenced a new academic year in February/March 2020 largely with "business as usual." The subsequent Covid-19 pandemic imposed unexpected disruptions to anatomical educational practice. Rapid change occurred due to government-imposed physical distancing regulations from March 2020 that increasingly restricted anatomy laboratory teaching practices. Anatomy educators in both these countries were mobilized to adjust their teaching approaches. This study on anatomy education disruption at pandemic onset within Australia and New Zealand adopts a social constructivist lens. The research question was "What are the perceived disruptions and changes made to anatomy education in Australia and New Zealand during the initial period of the Covid-19 pandemic, as reflected on by anatomy educators?." Thematic analysis to elucidate "the what and why" of anatomy education was applied to these reflections. About 18 anatomy academics from ten institutions participated in this exercise. The analysis revealed loss of integrated "hands-on" experiences, and impacts on workload, traditional roles, students, pedagogy, and anatomists' personal educational philosophies. The key opportunities recognized for anatomy education included: enabling synchronous teaching across remote sites, expanding offerings into the remote learning space, and embracing new pedagogies. In managing anatomy education's transition in response to the pandemic, six critical elements were identified: community care, clear communications, clarified expectations, constructive alignment, community of practice, ability to compromise, and adapt and continuity planning. There is no doubt that anatomy education has stepped into a yet unknown future in the island countries of Australia and New Zealand.